GAME-BASED LEARNING TO DEVELOP EARLY CHILDHOOD SOCIAL-EMOTIONAL COMPETENCE: CREATIVE STRATEGIES OF EARLY CHILDHOOD TEACHERS IN THE ERA OF INDEPENDENT LEARNING - Juniati Jusniar (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study aims to examine the implementation of game-based learning (GBL) as a creative strategy for early childhood teachers in developing early childhood social-emotional competencies in the era of Independent Learning. A descriptive qualitative approach was used to explore the learning practices carried out by teachers in several PAUD institutions, with data collection techniques in the form of observation, in-depth interviews, and documentation. The results of the study showed that GBL was applied through various educational games such as role plays, emotional cards, and group cooperation, which were designed to train empathy, emotion management, and children's relational skills. Teachers play an active role as facilitators who accompany the play process, as well as conduct reflective evaluations of children's development. Games that are carried out in a structured manner have been proven to have a positive impact on children's ability to interact socially and manage feelings. The teacher's creative strategy is also reflected in the use of simple game tools and traditional game modifications. This research confirms that GBL is a relevant and effective approach in the context of Freedom of Learning, as well as supporting the development of early childhood character in a comprehensive and sustainable manner.